Environmental policy through climate engineering? - Erik Gawel (Helmholtz-Zentrum für Umweltforschung (UFZ), 2014)
For years, humans have been trying to stabilize the world's environment by lowering the amount of greenhouse gases that their societies pump into the air. In 1992, this approach was even incorporated into the UN Framework Convention on Climate Change. But because this strategy failed to produce the desired results so far, technology-based processes designed to save the environment have emerged as a popular new weapon in the climate-protection arsenal. The question is: Are such climate-engineering efforts a viable environmental policy option? And can they serve, at the very least, as the ultima ratio if all other efforts to stave off climate change fail?
Keywords: 330